An economic analysis of integrated crop-livestock systems in Iowa, U.S.A. (October 2017) - Poffenbarger, Hanna; Artz, Georgeanne; Dahlke, Garland; Edwards, William; Hanna, Mark; Russell, James; Sellers, Harris; Liebman, Matt
Abstract: Diversified cropping systems integrated with livestock production can provide substantial soil conservation and water quality benefits, yet farmers in the U.S. Corn Belt have shifted toward greater specialization of farming systems in recent decades. The purpose of this study was to evaluate the economic feasibility of re-integrating crops and livestock in farming systems of the U.S. Corn Belt. Using data on farming practices and yields from a long-term cropping systems experiment, we calculated annual revenue and costs of four farming systems–a simple corn-soybean rotation with and without cattle (2-yr cash and 2-yr integrated, respectively) and a diversified corn-soybean-oat/alfalfa-alfalfa rotation with and without cattle (4-yr cash and 4-yr integrated, respectively). Our analysis was conducted for a 405-ha parcel in central Iowa over the period of 2008 to 2015. To maximize the use of harvested crops, cattle enterprises differed for the 2- and 4-yr rotations: yearlings were finished using a diet of mostly concentrate feeds for the 2-yr integrated system and calves were backgrounded and finished using a diet of forages and concentrates for the 4-yr integrated system. We found that mean annual returns to land and management were similar among all four farming systems ($790 ha − 1 averaged across the four systems). The integrated systems exhibited greater variability among years in returns to land and management than the cash systems. In addition, total costs excluding land and management were four- to nine-fold greater for the integrated crop-livestock systems than for the cash crop systems. Labor requirements increased with crop rotation diversification by 59% (4-yr cash vs. 2-yr cash) and with integration of cattle by 217% (2-yr integrated vs. 2-yr cash) or 232% (4-yr integrated vs. 2-yr cash). We concluded that diversified crop rotations with or without cattle are profitable farming systems in Iowa, but require greater capital and labor inputs than the dominant 2-yr cash grain system. Highlights: Integrated crop-livestock systems offer conservation benefits. Similar profits for simple and diversified crop rotations with and without cattle Higher costs for integrated crop-livestock systems than cash crop systems Higher labor inputs for integrated crop-livestock systems than cash crop systems